The Effect of Calcium Gluconate on Platelet Rich Plasma Activation for VEGF-A Expression of Human Dental Pulp Stem Cells - Margono, Anggraini; Bagio, Dini Asrianti; Julianto, Indah; Suprastiwi, Endang (European Journal of Dentistry, 2021)
Objective Platelet-rich plasma (PRP) activation is an important factor in triggering the initial release of blood-derived growth factors from platelets. Vascular endothelial growth factor-A (VEGF-A) can be expressed by human dental pulp stem cells (hDPSCs) and plays an important role in dental pulp angiogenesis. The aim of this study is to analyze the effects of calcium gluconate on PRP activation in hDPSC VEGF-A expression.Materials and Methods Two types of PRP and their corresponding activators were analyzed in this study: PRP (activated using calcium chloride/CaCl2) and PRP-T (activated using CaCl2 with the addition of 10% calcium gluconate). hDPSCs were obtained by using an out-growth method (DPSCs-OG), and harvest between the fifth and sixth passages, then cultured in three different media groups: control, PRP, and PRP-T, which were planted in 96 wells (5 × 103 each well). The VEGF-A expression of hDPSCs was analyzed by using an ELISA test and observed at 24, 48, and 72 hours.Statistical Analysis This study was performed by using one-way ANOVA (p < 0.05) test.Results There were significant differences between all groups (p < 0.05) at 48 and 72 hours of observations, and no significant differences in the PRP and PRP-T groups at 48 and 72 hours of observations (p > 0.05).Conclusion PRP and PRP-T were equally effective in inducing VEGF-A expression of hDPSCs.
Keywords: platelet rich plasma; activation; calcium gluconate; calcium chloride